Exploring Challenges and Solutions to Prevent and Overcome Bullying Behavior Among Vocational School Students - Wardah, Ani; Auliah, Nurul; Aminah, Aminah; Andriyani, Riya; Pebrianti, Novi (Bulletin of Counseling and Psychotherapy, 2024)
Bullying continues to be a significant problem in educational settings, adversely affecting the psychological, physical, and social well-being of kids. This study investigates the difficulties and solutions for preventing and mitigating bullying among Vocational High School (SMK) students in Banjarmasin, Indonesia. Data were gathered via written and semi-structured interviews with four guidance and counseling educators from public and private vocational institutions Using a qualitative research methodology and case study design. The thematic analysis identified three primary challenges: the perception of bullying as a "joke," the impact of social media and the social context, and the difficulties of emotional regulation in adolescents. In response to these difficulties, schools are adopting various strategic approaches, including traditional services, anti-bullying policies, a WhatsApp hotline for reporting incidents, and collaborative initiatives that include all stakeholders within the school community. This research underscores the significance of technology integration and community engagement in fostering a secure and inclusive educational atmosphere. These findings substantially enhance the formulation of successful educational policies and anti-bullying initiatives.